Peculiarities of Optoacoustic Excitation and Propagation of Plate Waves in Thin-Walled Оbjects - A. R. Baev; A. I. Metskovets; A. L. Mayorov; M. V. Asadchaya; A. V. Vorobey (Приборы и методы измерений)
Increasing the efficiency of non-destructive control of lamellar materials with single and double-layer structure is an urgent scientific and technical task. The aim of the work was to investigate the peculiarities of excitation and reception of plate waves (PW) in single-layer and two-layer materials by pulsed laser radiation in relation to detection of cracks in them and estimation of layer thickness at one-sided sounding. A methodology has been developed and experimental studies of the influence of moving the area of laser generation of PW over the surface of dural samples relative to the crack simulator of different depth with the subsequent reception of the signal at a characteristic angle of inclination have been carried out. A significant change in the structure of the wave front at localization of the moving wave source zone in the vicinity of the crack simulator was found, accompanied by a change in the ratio of extreme values of amplitudes of the received asymmetric mode Aextr up to 14–15 dB. At receiving the symmetric s0 mode the value of Aextr does not exceed 3–4 dB. The interpretation of this effect is given. A method and scheme of thickness measurement of twolayer materials with metallized coating and non-metallic base (glass-textolite) is proposed and developed, where samples with copper coating and glass-textolite base of different thickness are used as an example. In this case, the velocity or propagation time of PW, between two small aperture (non-directional) transducers with an acoustic base of 43 mm, is used as an informative parameter. In this case, the estimated sensitivity of the measured circuit to changes in the thickness of the metal coating is of 0.5 μm, and the base – twice as much.